International debt reexamined - Cline, William R. (Washington, DC : Institute for International Economics, 1995)
"Impressive study includes an historical review of causes of 1980s crisis, the various policy responses, and resulting impact. Extensive survey of debt crisis literature. Draws lessons from the past to be used for future policy formulation. Likely to be the definitive study on international debt"--Handbook of Latin American Studies, v. 57.
Vital signs for the debt strategy -- A decomposition analysis of debt forecasts in the 1980s -- Debt theory: a critical review of literature -- Evolution and evaluation of the debt strategy -- Economic adjustment and debt strategy in Latin America -- Debt problems in the 1990s: Russia, Eastern Europe, and Sub-Saharan Africa -- Capital markets in the 1990s -- Epilogue: the Mexican peso crisis of December 1994.
Includes bibliographical references (pages 507-521) and index.
Keywords: Debts, External -- Developing countries; Debt relief -- Developing countries; Debt relief -- Developing countries; Debts, External; external debt; debt consolidation; international borrowing; econometric model; structural adjustment; role of USA; role of IMF; role of World Bank; financial market; case study; statistical table; Debts, External -- Developing countries; Debt relief -- Developing countries; International debts; Eastern Europe; Latin America; Mexico; Peru; Russian Federation; Venezuela (Bolivarian Republic of); Debt relief -- Developing countries; bibliography; graph; literature survey